2013
DOI: 10.1016/j.jobcr.2013.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Salivary enzymes in peptic ulcer disease

Abstract: Peptic ulcerLactate dehydrogenase Peroxidase Amylase a b s t r a c t Aim: Peptic ulcer, the common disease of the upper gastro-intestinal tract, occurs in about 5e10% of the world's population. Therefore, diagnosis of trace disease progression with a noninvasive method is of prime importance in the field of healthcare research. The aim of this study was to evaluate the validity of salivary enzymes as noninvasive biomarkers for peptic ulcer. Materials and methods: In practice, 34 peptic ulcer patients and 30 he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Of those, salivary gland and pancreas secrete various enzymes and play multiple roles in the gastrointestinal tract, 105 , 106 and salivary enzymes have also been associated with some GI disorders, including PUD. 107 Because of the limited power of eQTL datasets (most tissues n < 500), we considered the SMR association with P SMR < 0.05 (nominally significant) and P HEIDI > 0.05 as significant in this study. Then, we determined if any SMR significant genes were shared between the diseases.…”
Section: Methodsmentioning
confidence: 99%
“…Of those, salivary gland and pancreas secrete various enzymes and play multiple roles in the gastrointestinal tract, 105 , 106 and salivary enzymes have also been associated with some GI disorders, including PUD. 107 Because of the limited power of eQTL datasets (most tissues n < 500), we considered the SMR association with P SMR < 0.05 (nominally significant) and P HEIDI > 0.05 as significant in this study. Then, we determined if any SMR significant genes were shared between the diseases.…”
Section: Methodsmentioning
confidence: 99%
“…4 Salivary fluid protects the oral cavity against detritus agents such as microorganisms, toxins and various oxidants. 5 We have previously found that the biochemistry of human saliva is altered in response to external and internal factors such as smoking, 6 vegetarian diet, 7 peptic ulcer 8 and Ramadan fasting. 9 Other investigators have shown that in vitro exposure to cigarette smoke could significantly decrease biological activity of some enzymes, both in plasma and in saliva.…”
Section: Introductionmentioning
confidence: 99%
“…Further support was obtained from other studies that indicated a potential relationship of PD with PUD [8] . Comparison of salivary enzymes between healthy subjects and patients with PUD showed that the latter group was associated with higher α-amylase activity compared to the control [9] . One of major risk factors for PUD is smoking which not only induce ulceration and increase acidity of the stomach but it was suggested as a predisposing factor for H. pylori gastric ulceration [10] .…”
Section: Introductionmentioning
confidence: 94%